Dietary shifts across ontogeny, regions and seasons in the red searobin, Prionotus nudigula , off Uruguay and northern Argentina - Jorge M. Roman; Andrea C. Lopez Cazorla; Santiago A. Barbini (Journal of Fish Biology, 2026)
The diet of Prionotus nudigula in coastal waters off Uruguay and northern Argentina (36°–41° S) and their variation in relation to body size, region and season were determined by analysis of stomach contents. Additionally, the trophic level of this species was estimated to establish its ecological role in this marine region. A total of 352 individuals were analysed, of which 308 (87.05%), ranging from 78 to 285 mm in total length (Lt), contained food. P. nudigula based its diet mainly on amphipods, followed by brachyuran crabs, shrimps and polychaetes. Cumaceans and isopods were also relevant prey but with a smaller contribution. Diet composition was strongly affected by body size and also by regions and seasons. Small individuals of P. nudigula consumed amphipods and small benthic fauna, whereas large individuals fed on brachyuran crabs, shrimps, cumaceans, hard benthic fauna and swimming prey. Furthermore, this species was able to consume larger brachyuran crabs and shrimps as it grew. P. nudigula exhibited regional and seasonal variations in its diet, showing changes in the consumption of its more important prey. Trophic level was 3.41, indicating that P. nudigula is a secondary consumer. This thorough investigation provides updated information on the trophic role of P. nudigula , representing a baseline for future investigations in the southwestern Atlantic Ocean.

Trophic ecology of the Argentine goatfish, Mullus argentinae (Mullidae) from off northern Argentina: ontogenetic and regional diet shifts - Jorge M. Roman; Andrea C. Lopez-Cazorla; Santiago A. Barbini (Environmental Biology of Fishes, 2026)

Modeling stochastic inflow patterns to a reservoir with hidden phase-type Markov model - M. L. Gamiz; D. Montoro-Cazorla; M. C. Segovia-Garcia (Environmental and Ecological Statistics, 2026)
This paper proposes a new statistical framework for modeling precipitation patterns in a specific geographic region using Hidden Markov Models (HMMs). Unlike conventional HMMs, where the hidden state process is Markovian, our approach introduces non-Markovian behavior by incorporating phase-type distributions to model state durations. This extension allows for a more realistic representation of alternating dry and wet periods, providing deeper insight into the temporal structure of the local climate. Building on this framework, we model reservoir inflow patterns linked to the hidden states and explain observed water storage levels through a Moran model. The analysis uses historical rainfall and inflow records, where inflows are influenced by latent climatic conditions rather than rainfall alone. By integrating these unobserved dynamics, the proposed model captures system complexity that would be missed by direct observation-based modeling. To evaluate performance, we compare our model against several standard ARIMA alternatives. The proposed PH-HMM achieves a substantially lower AIC (204.38) than the best ARIMA specification (211.91) and reduces mean squared error from 185.74 to 183.10. These improvements demonstrate that explicitly modeling regime dynamics yields more accurate and parsimonious representations of inflow processes. Overall, the methodology enhances characterization of underlying climatic regimes and improves inflow modeling, offering a practical tool for water resource management and climate adaptation planning.

Fe-Nx biomass-derived carbon material as efficient cathode electrocatalyst for alkaline direct methanol fuel cells - G. Alemany-Molina; V. Baglio; S. Campagna Zignani; A.S. Aricò; E. Morallón; D. Cazorla-Amorós; C. Lo Vecchio (Chemical Engineering Journal, 2025)

Feeding habits of a small demersal fish: Longfinned dwarf sea bass, Dules auriga (Teleostei: Serranidae), from the Southwest Atlantic - Jorge M. Roman; Andrea C. Lopez Cazorla; Santiago A. Barbini (Regional Studies in Marine Science, 2024)

Optimization of the Polarized Imaging Nephelometer (PI-Neph) for continuous monitoring of multiwavelength aerosol phase functions in support of space polarimetry missions - E. Bazo; J.V. Martins; D. Perez-Ramirez; A. Valenzuela; G. Titos; A. Cazorla; D. Fuertes; M. Weiss; A. Turpie; C. Li; F.J. García-Izquierdo; I. Foyo-Moreno; et al. (Atmospheric Environment, 2024)

Phenotypic correlates of structural and functional protein impairments resultant from ALDH5A1 variants - Itay Tokatly Latzer; Jean-Baptiste Roullet; Samuele Cesaro; Melissa L. DiBacco; Erland Arning; Alexander Rotenberg; Henry H. C. Lee; Thomas Opladen; Kathrin Jeltsch; Àngels García-Cazorla; Natalia Juliá-Palacios; K. Michael Gibson; et al. (Human Genetics, 2023)

Characterization of Tajogaite volcanic plumes detected over the Iberian Peninsula from a set of satellite and ground-based remote sensing instrumentation - V. Salgueiro; J.L. Guerrero-Rascado; M.J. Costa; R. Román; A. Cazorla; A. Serrano; F. Molero; M. Sicard; C. Córdoba-Jabonero; D. Bortoli; A. Comerón; F.T. Couto; et al. (Remote Sensing of Environment, 2023)

Ceratopogonidae (Diptera) Communities in a Protected Area Threatened by Urbanization - C. G. Cazorla; R. E. Campos (Neotropical Entomology, 2020)

Possible predation by the striped weakfish Cynoscion guatucupa on estuary-associated fishes in an Argentinian coastal lagoon - Gabriela E. Blasina; Andrea C. Lopez Cazorla; Juan M. DÍaz de Astarloa (Marine Biology Research, 2015)

Biological control of avocado white root rot with combined applications of Trichoderma spp. and rhizobacteria - D. Ruano-Rosa; F. M. Cazorla; N. Bonilla; R. Martín-Pérez; A. De Vicente; C. J. López-Herrera (European Journal of Plant Pathology, 2014)

Assessment of infection with polyomaviruses BKV, JCV and SV40 in different groups of Cuban individuals - Pedro A. Martínez; Vivian Kourí; Gustavo Cordero; Consuelo Correa; Yudira Soto; Virginia Capó; Licet González; Bienvenido Grá; Gregorio Petirena; César Silvério; Norma Hondal; Mabel González; et al. (Archives of Virology, 2012)

Is nasal carriage of Staphylococcus aureus the main acquisition pathway for surgical-site infection in orthopaedic surgery? - P. Berthelot; F. Grattard; C. Cazorla; J.-P. Passot; J.-P. Fayard; R. Meley; J. Bejuy; F. Farizon; B. Pozzetto; F. Lucht (European Journal of Clinical Microbiology & Infectious Diseases, 2010)

Biogeography of the Baetic ranges (SE Spain): A historical approach using cluster and parsimony analyses of endemic dolomitophytes - J. M. Medina‐Cazorla; J. A. Garrido‐Becerra; A. Mendoza Fernández; F. J. Pérez‐García; E. Salmerón; C. Gil; J. F. Mota Poveda (Plant Biosystems, 2010)

Q fever osteoarticular infection: four new cases and a review of the literature - C. Landais; F. Fenollar; A. Constantin; C. Cazorla; C. Guilyardi; H. Lepidi; A. Stein; J. M. Rolain; D. Raoult (European Journal of Clinical Microbiology & Infectious Diseases, 2007)

Arthroplastic and osteosynthetic infections due to Propionibacterium acnes: a retrospective study of 52 cases, 1995–2002 - M.-F. Lutz; P. Berthelot; A. Fresard; C. Cazorla; A. Carricajo; A.-C. Vautrin; M.-H. Fessy; F. Lucht (European Journal of Clinical Microbiology & Infectious Diseases, 2005)

Feeding habits of the juvenile striped weakfish, Cynoscion guatucupa Cuvier 1830, in Bahía Blanca estuary (Argentina): seasonal and ontogenetic changes - Paula Sardiña; Andrea C. Lopez cazorla (Hydrobiologia, 2005)

Effects of Cyprinus carpio on Potamogeton pectinatus in experimental culture: the incidence of the periphyton - N. S. Sidorkewicj; A. C. López Cazorla; O. A. Fernández; G. C. Möckel; M. A. Burgos (Hydrobiologia, 1999)

Interrelationships of fish and channel environmental conditions with aquatic macrophytes in an Argentine irrigation system - O. A. Fernández; K. J. Murphy; A. López cazorla; M. R. Sabbatini; M. A. Lazzari; J. C. J. Domaniewski; J. H. Irigoyen (Hydrobiologia, 1998)

Comparison of microbial tests for the detection of heavy metal genotoxicity - J. C. Codina; C. Pérez-Torrente; A. Pérez-García; F. M. Cazorla; A. de Vicente (Archives of Environmental Contamination and Toxicology, 1995)